2018
DOI: 10.3892/etm.2018.7081
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tenofovir disoproxil fumarate switch therapy in chronic hepatitis B patients with suboptimal response to adefovir‑based combination therapy

Abstract: In the present study, the efficacy and safety of tenofovir disoproxil fumarate (TDF) switch therapy were assessed in patients with chronic hepatitis B exhibiting a suboptimal response to adefovir (ADV)-based combination therapy. First, the efficacy of the TDF switch therapy was retrospectively evaluated in 50 patients with chronic hepatitis B who failed to respond to ADV-based combination treatment. Among those, 48 patients with a median age of 35 years were hepatitis B e antigen (HBeAg)-positive and 17, 14 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The median duration of combination therapy was 20.8 months and the median follow-up period was 24.7 months after switching to TDF monotherapy and all patients maintained CVR and switching from combination therapy to TDF monotherapy has been reported to be good in in virologically suppressed chronic hepatitis B [15]. Li et al [16] compared the efficacy of TDF switch therapy in 50 chronic hepatitis B patients with suboptimal response to ADV-based combination therapy. Among them 17, 14 and 19 patients were previously treated with LAM plus ADV, LdT plus ADV and ETV plus ADV, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median duration of combination therapy was 20.8 months and the median follow-up period was 24.7 months after switching to TDF monotherapy and all patients maintained CVR and switching from combination therapy to TDF monotherapy has been reported to be good in in virologically suppressed chronic hepatitis B [15]. Li et al [16] compared the efficacy of TDF switch therapy in 50 chronic hepatitis B patients with suboptimal response to ADV-based combination therapy. Among them 17, 14 and 19 patients were previously treated with LAM plus ADV, LdT plus ADV and ETV plus ADV, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, three patients (two of treated with TDF and one of with TDF plus ETV) had suboptimal response and six patients (five of received TDF and one of received TDF plus ETV) had virologic breakthrough. They reported that TDF switch therapy is efficient and safe for patients with chronic hepatitis B with a suboptimal response to ADV-based combination therapy [16].…”
Section: Discussionmentioning
confidence: 99%